Fine structure and morphology of sterlet (Acipenser ruthenus L. 1758) spermatozoa and acrosin localization - Psenicka, Martin; Vancova, Marie; Koubek, Pavel; Tesitel, Jakub; Linhart, Otomar (Animal reproduction science, 2009)
Ultrastructure of sterlet Acipenser ruthenus L. 1758 sperm was examined by scanning and transmission electron microscopy, which allowed us to use various methods for visualizations of different parts of sterlet spermatozoa. Sperm cells possess a head with a distinct acrosome, a midpiece and a single flagellum surrounded by the flagellar plasma membrane. The average length of the head including the acrosome and the midpiece was estimated as 5.14+/-0.42 microm. Nine to 10 posterolateral projections were derived from the acrosome. Three inter-twining endonuclear canals bounded by membranes traversed the nucleus in its whole length from the acrosome to the implantation fossa. Acrosin was located in all the three parts (acrosome, endonuclear canals and implantation fossa). The proximal and distal centrioles located in the midpiece compacted of nine peripheral triplets of microtubules. One cut of the midpiece contained from two to six mitochondria with area of 215+/-85 nm(2) in average. The flagellum was 42.47+/-1.89 microm in length with typical eukaryotic organization of one central pair and nine peripheral pairs of microtubules. It passed through a cytoplasmic channel in the midpiece, which was formed by an invagination at the plasmalemma. The flagellum gradually developed two lateral extensions of its plasma membrane, so-called "fins". Detected morphological variation can be described by four principal component axes corresponding to groups of individual morphometric characters defined on the sperm structures. Correlations among the characters indicate that the sperms are variable in their shape rather than size. Significant variation among examined fish individuals was found only in flagellum and nucleus length. Comparison between the present and previous studies of morphology of sturgeon spermatozoa confirmed large inter- and/or intra-specific differences that could be of substantial taxonomic value.
Keywords: hlavička spermie; Male; akrozom; akrosin; bičík spermie; Spermatozoa; mužské pohlaví; analýza hlavních komponent; Sperm Tail; ryby; Principal Component Analysis; Acrosome; Fishes; Animals; Microscopy, Electron, Transmission; Microscopy, Electron, Scanning; zvířata; Sperm Head; spermie; Acrosin; mikroskopie elektronová rastrovací; transmisní elektronová mikroskopie